Mitigation of earthquake induced geotechnical hazards using tire waste-sand mixtures - Adır, Korhan. (Thesis (M.S.) - Bogazici University. Kandilli Observatory and Earthquake Research Institute, 2013., 2013)
Seismic Isolation Systems are among tools to achieve advanced earthquake-resistant designs, developed in last century. Commonly, the applications are seen in cases which it is aimed to stabilize structures considered to have critical and expensive content in front of a strong ground motion. Recently, an alternative technique for seismic protection had been proposed involving mixing soil with tire waste and so improving the mixture’s dynamic properties, than placing it around structures foundations. This soil improvement called as Geotechnical Seismic Isolation (GSI) is supposed to improve especially damping property. It is claimed that, when placed to underlying soil layer of a structure subject to seismic movement, it would level down the soil’s seismic movement transmittancy. This study investigates the applicability of GSI with numerical analysis. Reprocessed Tire Waste-Sand Mixtures (TWSM) from Tire Buffings and Tire Crumbs; of which, mechanical and dynamic properties were revealed for different mixing proportions; are chosen as GSI material alternatives. A finite element program developed as a plug-in on QUAD4M, Equivalent Linear Analysis (ELA) Software, able to model structure-subsoil system is used to perform numerical analyses with the TWSM experimental data. In the results of numerical analyses, TWSM use as GSI material is examined regarding the effect of structure’s number of storey, weight ratio of tire crumb over TWSM, different earthquake records, changing TWSM layer thickness, and pile foundation. During analysis, different earthquake records have been applied to TWSM-structure systems differed in reinforced concrete structure rise (low-medium), and soil layer; different depths of TWSM and pile foundation. Reduction of acceleration motions of rigid structure and inter-storey drift are selected as performance indicators. Results are investigated to reveal the effect of TW inclusion to earthquake induced soil standing under a low-medium rise structure and to comment the functionality of the use of improved soil as geotechnical seismic isolation.
Keywords: Earthquake hazard analysis.; Earthquake engineering.; Reliability (Engineering)